Use of intravascular ultrasound for optimal vessel sizing in chronic total occlusion percutaneous coronary intervention - Blessing, Recha; Buono, Andrea; Ahoopai, Majid; Geyer, Martin; Knorr, Maike; Brandt, Moritz; Steven, Sebastian; Drosos, Ioannis; Muenzel, Thomas; Wenzel, Philip; Gori, Tommaso; Dimitriadis, Zisis (Frontiers in Cardiovascular Medicine, 2022)
Aim The aim of this study is to provide evidence on how use of standardized intravascular ultrasound (IVUS) use impacts stent size choice in the setting of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) compared to visual estimation. Methods and results Data of 82 consecutive patients who had successfully undergone IVUS-guided revascularization of CTO at the University Medical Center Mainz were analyzed. Angiography-based stent size prediction for the proximal and distal vessels was compared to the implanted stent diameter after IVUS assessment. Angiography-based stent size prediction for the proximal vessel was 3.09 ± 0.41, whereas IVUS use demonstrated larger vessel diameter, resulting in larger implanted stent diameter (3.24 ± 0.45, p < 0.001). Proximal vessel stent size prediction was underestimated in the majority of patients by angiographic estimation. Angiography-based stent size prediction for the distal vessel was 2.79 ± 0.38, whereas IVUS use demonstrated larger vessel diameter, resulting in larger implanted stent diameter (2.92 ± 0.39, p < 0.001). Conclusion Pre-stent IVUS assessment in CTO PCI provides important information on vessel morphology and size. Angiography-based stent size prediction for the proximal and distal vessels was frequently underestimated, IVUS use demonstrated larger vessel diameter, resulting in significantly larger implanted stent diameter.